2013
DOI: 10.5194/tc-7-1399-2013
|View full text |Cite
|
Sign up to set email alerts
|

Snow on the Ross Ice Shelf: comparison of reanalyses and observations from automatic weather stations

Abstract: Abstract. Snow accumulation measurements from automatic weather stations (AWS) around the Ross Ice Shelf (RIS), Antarctica, are used to provide a new set of groundbased observations which are compared to precipitation from the ECMWF ERA-Interim and NCEP/NCAR Reanalysis-2 datasets. The high temporal resolution of the AWS snow accumulation measurements allow for an event-based comparison of reanalyses precipitation to the in situ observations. Snow accumulation records from nine AWS provide multiple years of acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Considering high‐precipitation days and high snow accumulation days at Halvfarryggen and Kohnen only, we come to the following conclusions: while high‐precipitation days in the AMPS data set are generally captured by ERA‐Interim, high‐precipitation days in ERA‐Interim do only correspond to high snow accumulation days in the AWS data in 16% (9%) of the cases at Halvfarryggen (Kohnen). These percentages are lower than those found by Cohen and Dean [] in their comparison of ERA‐Interim precipitation with snow accumulation measurements from AWSs located on the Ross Ice Shelf, Antarctica. Possible reasons for that could be the different definition for precipitation and accumulation events they used, the less complex terrain of the Ross Ice Shelf which is better represented in the reanalysis compared to, e.g., Halvfarryggen, and different wind conditions on the Ross Ice Shelf influencing the snow redistribution at the AWSs.…”
Section: Discussion and Main Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering high‐precipitation days and high snow accumulation days at Halvfarryggen and Kohnen only, we come to the following conclusions: while high‐precipitation days in the AMPS data set are generally captured by ERA‐Interim, high‐precipitation days in ERA‐Interim do only correspond to high snow accumulation days in the AWS data in 16% (9%) of the cases at Halvfarryggen (Kohnen). These percentages are lower than those found by Cohen and Dean [] in their comparison of ERA‐Interim precipitation with snow accumulation measurements from AWSs located on the Ross Ice Shelf, Antarctica. Possible reasons for that could be the different definition for precipitation and accumulation events they used, the less complex terrain of the Ross Ice Shelf which is better represented in the reanalysis compared to, e.g., Halvfarryggen, and different wind conditions on the Ross Ice Shelf influencing the snow redistribution at the AWSs.…”
Section: Discussion and Main Conclusionmentioning
confidence: 99%
“…[] argued that the ERA‐Interim data set provides the most realistic depiction of precipitation variability in high southern latitudes since 1989, compared to other contemporary reanalyses. Cohen and Dean [] evaluated how well ERA‐Interim and the National Centers for Environmental Prediction/Department of Energy Atmospheric Model Intercomparison Project 2 reanalysis (NCEP 2) represent precipitation over the Antarctic Ross Ice Shelf on synoptic time scales by comparing precipitation data from these two reanalyses with snow accumulation measurements from AWSs. They found that ERA‐Interim reproduces more precipitation events and also produces more precipitation per event than NCEP 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AWSs provide the most efficient way of acquiring snow accumulation measurements for the AIS at a high temporal resolution (ten-minute) [22]. AWS snow accumulation has been used to examine the variability of the SMB, the characteristics of extreme precipitation events and the performance of reanalysis data and regional climate models [7,[23][24][25][26]. While the number of stations is small at present and measurements are influenced by wind, AWS data are essential for a better understanding of the Antarctic SMB and high precipitation events at a synoptic timescale [23,25,26].…”
mentioning
confidence: 99%
“…AWS snow accumulation has been used to examine the variability of the SMB, the characteristics of extreme precipitation events and the performance of reanalysis data and regional climate models [7,[23][24][25][26]. While the number of stations is small at present and measurements are influenced by wind, AWS data are essential for a better understanding of the Antarctic SMB and high precipitation events at a synoptic timescale [23,25,26]. SMB contains snowfall which is the main positive term of the SMB, surface sublimation, drifting snow sublimation, surface melt and wind-induced accumulation or ablation by drifting and blowing snow [4,5].…”
mentioning
confidence: 99%